UPAYA MENINGKATKAN KEMAMPUAN MEMBACA SISWA DENGAN MENGGUNAKAN PENDEKATAN WHOLE LANGUAGE PADA SISWA KELAS 1 SDN TANJUNG JATI 2: EFFORTS TO IMPROVE STUDENTS' READING SKILLS BY USING THE WHOLE LANGUAGE APPROACH IN GRADE 1 STUDENTS OF SDN TANJUNG JATI 2 - Agustin, Cindy Erra; Setyawan, Agung (PANDU : Jurnal Pendidikan Anak dan Pendidikan Umum, 2023)
The purpose of this study is to determine whether the whole language approach at SDN Tanjung Jati 2, located in Kamal Sub-district, Bangkalan Regency, has improved the reading skills of first grade students. This research is a classroom action study, where students and tests are directly observed to collect data. Two research cycles were conducted: the first cycle and the second cycle. The research findings show that the children's reading skills have improved. The percentage of students who met the Minimum Competency Criteria (KKM) increased from 30% in the first cycle to 78% in the second cycle. These results support the idea that teaching Indonesian through the whole language method can improve students' reading comprehension.